Using of Appropriated Strains in the Practice of Compost Supplementation for Agaricus subrufescens Production - Zied, Diego C.; Caitano, Cinthia E. C.; Pardo-Gimenez, Arturo; Dias, Eustáquio S.; Zeraik, Maria L.; Pardo, Jose E. (Frontiers in Sustainable Food Systems, 2018)
The aim of this study was to analyse the viability of supplementation of Agaricus subrufescens compost with different organic materials, using 3 commercial strains. Compost was prepared by the traditional method and was used as a control (without supplemented). Six supplements were applied and can be separated into 4 categories: i) commercial supplements (recommended for Agaricus bisporus and Pleurotus ostreatus); ii) supplements based on agro-industrial waste (provided by peanut and acerola juice); iii) supplements based on noble grains (a mix with bran of soybean, corn and cotton); and iv) a blend of supplements ii and iii (peanut waste, acerola juice waste, and noble grains - a mixture of 33.3% each). The results showed that the practice of supplementation is an important tool to improve the yield in the industrial production of A. subrufescens. Waste materials and noble grains can be selected as quality supplements. The use of appropriated strains is essential for the success of the supplementation practice.